2016
DOI: 10.18805/lr.v0iof.3546
|View full text |Cite
|
Sign up to set email alerts
|

Compost effects on leaf area index and seed production enhancement in an important arid land leguminous tree Acacia tortilis subsp. Raddiana

Abstract: This study aimed to investigate the effects of compost addition on leaf area index (LAI), diameter growth and enhancement of seed production and quality in Acacia tortilis established under supplementary drip irrigation. Three composted fertilizer doses (2.5 kg, 5 kg and 7.5 kg/ tree) were compared to NPK (18-18-5 at a rate of 250 gram per tree) and control unfertilized plots. Effects of compost application on leaf area index (LAI), diameter growth, relative monthly diameter increment (RMDI) were monitored dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Meanwhile, the leaf area and total yield of B. rapa production for TF and MF treatments showed a double increment. Elfeel and Abohassan (2016) reported that the NPK fertilizer used for plants has a higher leaf area index value. The higher value of leaf area indicates higher plant weight that affects the results of yield obtained.…”
Section: Growth Performance Of B Rapa With Compostmentioning
confidence: 99%
“…Meanwhile, the leaf area and total yield of B. rapa production for TF and MF treatments showed a double increment. Elfeel and Abohassan (2016) reported that the NPK fertilizer used for plants has a higher leaf area index value. The higher value of leaf area indicates higher plant weight that affects the results of yield obtained.…”
Section: Growth Performance Of B Rapa With Compostmentioning
confidence: 99%